Redenomination of the Indonesian Rupiah: A Legal-Policy Analysis from a Maqāṣid Perspective - Iffatin Nur; Reni Dwi Puspitasari; Indri Hadisiswati; Divia Nur Alan Nur Ilmas (International Journal of Law and Society, 2025)
This article examines the proposed redenomination of the Indonesian Rupiah through a normative–conceptual legal-policy analysis informed by the Maqāṣid al-Sharīʿah framework. The study evaluates the legal foundations, philosophical justification, and policy implications of redenomination within Indonesia’s current macroeconomic and institutional context. Drawing on primary legal materials such as Law No. 7 of 2011 on Currency, Bank Indonesia regulations, and Ministry of Finance instruments alongside doctrinal writings and legal-philosophical scholarship, the research integrates doctrinal interpretation, legal-policy analysis, and maqāṣid reasoning. The findings indicate that redenomination is normatively grounded in constitutional mandates to ensure currency sovereignty and monetary stability. It enhances transactional efficiency, supports price transparency, and strengthens currency credibility when implemented under stable macroeconomic conditions. From the Maqāṣid framework, redenomination aligns with ḥifẓ al-māl (protection of wealth), al-ʿadālah (justice), and maṣlaḥah (public welfare). This study contributes an interdisciplinary framework bridging legal doctrine, public policy, and Islamic legal philosophy. Limitations arise from reliance on secondary sources, indicating the need for empirical and comparative research.